When Acehnese Meets English: An Optimality-Theoretic Analysis of Phonological Interference in Multilingual Learners at IAIN Langsa - Dedy Suhery; Zahratul Idami; Israul Husna; Muhd Hamid Raza (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Multilingualism in Indonesia is a daily reality, with individuals frequently shifting between languages and dialects. At Institut Agama Islam Negeri (IAIN) Langsa, students in the English Education Department embody this dynamic environment, speaking Acehnese (L1), Bahasa Indonesia (L2), and English (L3). This study investigates how Optimality Theory explains the phonological patterns shaped by multilingual interaction. Data were collected through fieldwork, interviews, and audio recordings of four students, focusing on phonological interference and multilingual dynamics. Findings reveal that language contact strongly influences English pronunciation. The Acehnese phonological system, in particular, affects how learners articulate English sounds. The most consistent interference involves the voiceless alveolar stop /t/, which is aspirated as [tʰ] in word-initial and medial positions but not in final position. Examples include table /ˈteɪ.bəl/ → [ˈtheɪ.bəl], cutie /ˈkjuː.ti/ → [ˈkjuː.thi], and tooth /toːθ/ → [toːθ], with /θ/ often replaced by [t]. These patterns highlight systematic transfer of phonetic features—aspiration, intonation, and accent—from L1 into English. Such interference complicates mastery of English phonology, underscoring the profound role of L1 influence in multilingual speech production and the challenges learners face in aligning with target-language norms.